2014
DOI: 10.7453/gahmj.2014.046
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Food Elimination Diet on Collegiate Athletes’ 300-meter Run Time and Concentration

Abstract: Background:Optimal human function and performance through diet strategies are critical for everyone but especially for those involved in collegiate or professional athletics. Currently, individualized medicine (IM) is emerging as a more efficacious approach to health with emphasis on personalized diet strategies for the public and is common practice for elite athletes. One method for directing patient-specific foods in the diet, while concomitantly impacting physical performance, may be via IgG food sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[40][41][42] Previous studies have demonstrated that elimination diets can improve measures of cognition and sleep, which is strongly associated with mental health and quality of life. [25,[65][66][67] While this study did not directly evaluate the sleep of participants, the research team hypothesizes that enhanced sleep may be one of the mechanisms underlying the dramatic mental health improvements in both arms of this study.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Previous studies have demonstrated that elimination diets can improve measures of cognition and sleep, which is strongly associated with mental health and quality of life. [25,[65][66][67] While this study did not directly evaluate the sleep of participants, the research team hypothesizes that enhanced sleep may be one of the mechanisms underlying the dramatic mental health improvements in both arms of this study.…”
Section: Discussionmentioning
confidence: 99%